INFLUENCE OF STORAGE MEDIA ON THE VITALITY OF STEM CELLS FROM APICAL PAPILLA - Krasimir Hristov; Natalia Gateva; Pavel Stanimirov; Nikolay Ishkitiev; Rozaliya Tsikandelova (Peytchinski Publishing, 2018)
Purpose: Immediate replantation is the treatment of choice for avulsed permanent teeth. Transportation of avulsed teeth to the dentist office requires storage in suitable media, thus keeping periodontal and periapical tissues viable. Effect of different storage media on periodontal cells vitality has been thoroughly researched, but there is no available data concerning SCAP. The purpose of this study is to evaluate the storage media effect on SCAP vitality. Materials and methods: Our study includes 10 third molars of 14-17 years old patients, extracted due to orthodontic reasons. The apical papilla of those teeth is handled according to protocol, and the cell growth is maintained in DMEM. Cells are divided into 4 groups: 1-positive control group, 2- SOS Dentobox, 3 - (HBSS), 4 - negative control group. A colourimetric assay was used to determine the vital cell count in each group. Results: Signal strength of the cells, stored in SOS Dentobox, is on average 30% weaker than the positive control group cells' signal, while the signal strength of the cells, stored in HBSS, is 65,2% weaker. Conclusion: SOS Dentobox provides better SCAP cell vitality than HBSS